Security in Wireless sensor network: Approaches and Issues - Raja Waseem Anwar; Majid Bakhtiari; Anazida Zainal; Kashif Naseer Qureshi (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Wireless sensor network is a tremendous emerging technology provides communication services for environmental monitoring and target tracking for mass public and military. With increasing of this smart network popularity sensor network faced various challenges and threats. The inclusion of wireless sensor nodes also incurs different types of security threats in network. Mostly networks are using shared key approaches to make less communication overhead, but still network compromise with replay impersonation and compromise attacks. The existing proposed schemes are not fully addressed other network resources such as energy and speed, etc.  The intent of this paper is to provide a comprehensive security requirement, detail about security attacks in network and discuss the existing security schemes.